KOOP Online Ordering Management System at Kolej Kediaman Tun Dr Ismail, UTHM - YAZID, SITI AINUL BASYEERA; MOHD YASIN, SUHAILA (Applied Information Technology And Computer Science, 2025)
The KOOP Online Ordering Management System enhances business productivity and simplifies the shopping experience for customers. By transitioning from traditional in-store shopping to an online platform, productivity is boosted, and customers can conveniently browse and purchase items. The system features user registration, item catalogs, payment options, and order pickup functionalities. Implemented in HTML, CSS, PHP, and JavaScript through Microsoft Visual Studio, with MySQL managing the database, the system enables customers to place orders anytime, anywhere, while providing effective stock control for the shop owner. This transition is expected to increase sales and streamline the customer experience.